Зависимость эффективности биологической обратной связи по параметрам ритма сердца от вариаций геомагнитного поля - Григорьев, П.Е.; Поскотинова, Л.В. (Таврический медико-биологический вестник, 2009)
Протягом багатоденного моніторингу біологічного зворотного зв’язку (БЗЗ) за

параметрами варіабельності серцевого ритму встановлено залежність

ефективності БЗЗ від геліогеофізичної обстановки. У випробуваних з

переважанням симпатичної активності є тенденція до більш ефективного

біоуправління в умовах геомагнітної збуреності а також стабільного напряму

міжпланетного магнітного поля. Навпаки, у випробуваних з переважанням вагусної

активності БЗЗ є ефективнішім за умов відсутності геомагнітних збурювань а також

при змінах полярності міжпланетного магнітного поля. Таким чином,

геліогеофізичну обстановку слід ураховувати при аналізі ефективності

біоуправління. Through days-long monitoring of biofeedback parameters of heart rate variability the

dependence of biofeedback effectiveness on the geocosmic factors was established. In

subjects whose nervous system is dominated by sympathetic type of reactivity, the

biofeedback effectiveness tends to a better biocontrol under conditions of changes in

interplanetary magnetic field or conditions of stable orientation of the interplanetary

geomagnetic field. Individuals with prevalence of vagal activity usually are more

effective in the biofeedback session if there are no geomagnetic disturbances as well

as under conditions of changes in the interplanetary magnetic field polarity. Thus, the

geocosmic factors should be taken into account when biofeedback effectiveness is

analyzed.